2001
DOI: 10.1128/jb.183.5.1796-1800.2001
|View full text |Cite
|
Sign up to set email alerts
|

The miaA Mutator Phenotype of Escherichia coli K-12 Requires Recombination Functions

Abstract: miaA mutants, which contain A-37 instead of the ms 2 i 6 A-37 hypermodification in their tRNA, show a moderate mutator phenotype leading to increased GC3TA transversion. We show that the miaA mutator phenotype is dependent on recombination functions similar to, but not exactly the same as, those required for translation stress-induced mutagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(40 reference statements)
0
15
0
1
Order By: Relevance
“…The mutA allele differs from the wild-type (glyV ϩ ) tRNA gene by a single base substitution that alters the anticodon in such a way as to promote Asp3Gly mistranslation in mutA cells. Subsequent to this finding, other work revealed that mutations in many other genes that specify tRNAs (10,26) or tRNA-modifying enzymes (32) lead to a similar phenotype presumably mediated by mistranslation. Moreover, exposure to streptomycin, an antibiotic known to promote mistranslation, induces a very similar phenotype in cells bearing certain mutations in rpsL, the gene specifying the 30S ribosomal protein S12 (6).…”
mentioning
confidence: 99%
“…The mutA allele differs from the wild-type (glyV ϩ ) tRNA gene by a single base substitution that alters the anticodon in such a way as to promote Asp3Gly mistranslation in mutA cells. Subsequent to this finding, other work revealed that mutations in many other genes that specify tRNAs (10,26) or tRNA-modifying enzymes (32) lead to a similar phenotype presumably mediated by mistranslation. Moreover, exposure to streptomycin, an antibiotic known to promote mistranslation, induces a very similar phenotype in cells bearing certain mutations in rpsL, the gene specifying the 30S ribosomal protein S12 (6).…”
mentioning
confidence: 99%
“…Characteristically, mutations in miaA cause broad pleiotropic phenotypes, including decreased growth rate and yield, broad changes in the biosynthesis and utilization of certain amino acids, defects in translation efficiency and fidelity (especially of specific regulatory genes), increased susceptibility to antibiotics and reduced virulence [32,54]. For example, cellular yields of miaA mutants in S. enterica sv.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of miaA results in an ϳ50-fold increase in GC ¡ TA transversions (31) ( Table 2). While the cascade of events that promotes mutations in ⌬miaA mutant populations is far from clear, several clues indicate that it is associated with translational stress-induced mutagenesis (33). Our screen also identified a central regulator of iron homeostasis (fur) (35) whose removal yields a mutator phenotype.…”
mentioning
confidence: 94%
“…Defects in and downregulation of these genes are frequently associated with pathogenic populations, indicating a central role for this pathway during bacterial adaptation in nature (22,24,32). Second, defects in tRNA modification due to miaA deletion cause reduced fidelity and efficiency of translation (33). This gene encodes a tRNA dimethylallyltransferase and is involved in hypermodification of the A37 base of certain tRNAs (34).…”
mentioning
confidence: 99%